Health Literacy Assessment of the STOFHLA: Paper Versus Electronic Administration Continuation Study. (February 2014) - Chesser, Amy K.; Keene Woods, Nikki; Wipperman, Jennifer; Wilson, Rachel; Dong, Frank
Low health literacy is associated with poor health outcomes. Research is needed to understand the mechanisms and pathways of its effects. Computer-based assessment tools may improve efficiency and cost-effectiveness of health literacy research. The objective of this preliminary study was to assess if administration of the Short Test of Functional Health Literacy in Adults (STOFHLA) through a computer-based medium was comparable to the paper-based test in terms of accuracy and time to completion. A randomized, crossover design was used to compare computer versus paper format of the STOFHLA at a Midwestern family medicine residency program. Eighty participants were initially randomized to either computer ( n = 42) or paper ( n = 38) format of the STOFHLA. After a 30-day washout period, participants returned to complete the other version of the STOFHLA. Data analysis revealed no significant difference between paper- and computer-based surveys ( p = .9401; N = 57). The majority of participants showed "adequate" health literacy via paper- and computer-based surveys (100% and 97% of participants, respectively). Electronic administration of STOFHLA results were equivalent to the paper administration results for evaluation of adult health literacy. Future investigations should focus on expanded populations in multiple health care settings and validation of other health literacy screening tools in a clinical setting.